A novel zirconium-based halide inorganic solid-state electrolyte and a preparation method and application thereof
Patent Information
- Application Number
- CN202610420119.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-01
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-04-01
AI Technical Summary
[0004]然而,现有卤化物固态电解质的发展面临以下瓶颈,严重制约其商业化推广:高离子电导率的卤化物电解质(如Li3InCl6、Li3ScCl6)往往含有稀土金属元素,原料成本高昂;而低成本的锆基卤化物(如Li2ZrCl6)未经过优化掺杂时,室温离子电导率低0.3-0.8mS/cm,难以满足实用化要求;且制备工艺中存在混合不均、掺杂离子团聚、无定形结构稳定性差等问题
1.本发明以Li2ZrCl6为基体,通过Cd2+阳离子掺杂与O2-阴离子共掺的双掺杂策略,结合无定形结构调控,使锆基卤化物固态电解质在30℃下的离子电导率提升至1.8×10-3S/cm,同时电子电导率控制在≤6.66×10-9S/cm,显著优化了电解质的离子传输性能与电子绝缘性,为全固态锂离子电池的室温稳定循环提供了核心支撑;
Smart Images

Figure CN121948536B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of all-solid-state lithium-ion battery technology, specifically relating to a novel zirconium-based halide inorganic solid electrolyte, its preparation method, and its application. Background Technology
[0002] With the development of energy and efficient energy storage technologies, all-solid-state lithium-ion batteries are gradually replacing traditional liquid lithium-ion batteries and becoming the cornerstone of large-scale energy storage systems. Solid-state electrolytes, as a crucial component of all-solid-state lithium-ion batteries, need to balance the following characteristics: high ionic conductivity, a wide electrochemical window, excellent chemical stability, and low cost.
[0003] Among current mainstream solid-state electrolytes, polymer electrolytes have low intrinsic ionic conductivity, making them unsuitable for high-power applications; oxide electrolytes, while electrochemically stable, require high-temperature sintering, resulting in complex manufacturing processes and high interfacial impedance with the electrode; sulfide electrolytes exhibit excellent ionic conductivity, but suffer from poor oxidative stability, readily reacting with high-voltage cathodes and decomposing to produce toxic gases in humid environments, limiting their practical applications. In contrast, halide solid-state electrolytes, with their high room-temperature ionic conductivity, good mechanical flexibility, and compatibility with high-voltage cathodes, have become one of the optimal candidates for balancing performance and safety.
[0004] However, the development of existing halide solid electrolytes faces the following bottlenecks, which seriously restrict their commercialization: high ionic conductivity halide electrolytes (such as Li3InCl6 and Li3ScCl6) often contain rare earth metal elements, resulting in high raw material costs; while low-cost zirconium-based halides (such as Li2ZrCl6) have low room temperature ionic conductivity of 0.3-0.8 mS / cm when not optimized for doping, making it difficult to meet practical requirements; and the preparation process suffers from problems such as uneven mixing, dopant ion agglomeration, and poor stability of amorphous structures.
[0005] Therefore, there is a need for a novel zirconium-based halide inorganic solid electrolyte and its preparation method to obtain a low-cost solid electrolyte that combines high ionic conductivity with extremely low electronic conductivity. Summary of the Invention
[0006] To address the aforementioned shortcomings in the existing technology, this invention provides a novel zirconium-based halide inorganic solid electrolyte, its preparation method, and its application, thereby solving the problems mentioned in the background technology.
[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A novel method for preparing zirconium-based halide inorganic solid electrolytes includes the following steps: Step 1: Under an inert protective atmosphere, weigh lithium source, zirconium source, cadmium source and oxygen source according to stoichiometric ratio; mix the raw materials in an agate mortar and perform pulsed ultrasonic-assisted gradient grinding to obtain an activated precursor mixture; Step 2: Add the precursor mixture to a zirconia ball mill jar, and ball mill it by applying an alternating electromagnetic field, while simultaneously and dynamically controlling the pressure and temperature inside the ball mill jar during the ball milling process; Step 3: After ball milling, the powder is transferred to an agate mortar and ground for 10-30 minutes in an inert atmosphere, followed by low-temperature plasma activation treatment, and inorganic solid electrolyte powder is collected. The general chemical formula of the novel zirconium-based halide inorganic solid electrolyte is Li a Zr b Cd c Cl x O y The microstructure is Zr 4+ Cd 2+ Amorphous structures with mixed arrangement.
[0008] Furthermore, in step 1, the lithium source is LiCl, the zirconium source is ZrCl4, the cadmium source is CdCl2, and the oxygen source is Li2O; and the amount of CdCl2 and Li2O weighed is 2-10% excess based on stoichiometry; the inert protective atmosphere is argon, with an oxygen content <0.01ppm and a water content <0.01ppm; in step 2, the grinding jar and grinding beads are both made of zirconium oxide; the diameter of the grinding beads used is 3-10mm; the ball-to-material ratio ranges from 10 to 40:1, i.e., the ratio of the total mass of the grinding beads to the total mass of the material to be ground is controlled within the range of 10:1 to 40:1.
[0009] Furthermore, the pulsed ultrasound-assisted gradient grinding process in step 1 includes grinding at a speed of 50-100 rpm for 5-10 minutes; then simultaneously performing intermittent pulsed ultrasound and high-speed grinding, wherein the pulsed ultrasound power is 150-250W, the frequency is 20-40kHz, and the cycle is 30 seconds working followed by a 30-second pause; the high-speed grinding is performed at a speed of 200-300 rpm for 5-20 minutes.
[0010] Furthermore, the alternating electromagnetic field in step 2 is a sinusoidal alternating electromagnetic field with a magnetic field strength of 20-40 mT and a frequency of 100-200 Hz; the pressure inside the ball mill jar is 0.1-0.2 MPa; the ball milling process is divided into two stages. In the first stage, the magnetic field strength is 20-25 mT, the frequency is 100-150 Hz, the temperature is 25℃, and the rotation speed is 350-400 rpm, using a bidirectional ball milling mode for 8-12 hours. In the second stage, the magnetic field strength is 30-40 mT, the frequency is 150-200 Hz, the temperature is 45-55℃, and the rotation speed is 500-550 rpm, using a bidirectional ball milling mode for 12-20 hours. During the ball milling process, the equipment is shut down every 4 hours, the agglomerated powder on the inner wall of the ball mill container is scraped off, and argon gas is added.
[0011] Furthermore, the bidirectional ball milling mode involves first rotating in either clockwise or counterclockwise direction for 5-30 minutes, pausing for 5-30 minutes, then rotating in the opposite direction for 5-30 minutes, pausing for 5-30 minutes, and repeating this cycle.
[0012] Furthermore, the low-temperature plasma activation treatment in step 3 is carried out in an argon atmosphere, with a plasma activation power of 80-150W and a treatment time of 3-8 minutes.
[0013] A novel zirconium-based halide inorganic solid electrolyte is prepared by a novel method for preparing zirconium-based halide inorganic solid electrolytes. The general chemical formula of the novel zirconium-based halide inorganic solid electrolyte is Li. a Zr b Cd c Cl x O y Where 2≤a≤4, 0.8≤b≤1, 0≤c≤0.2, 4≤x≤6, 0≤y≤1.6; at a temperature of 30℃, the ionic conductivity of the inorganic solid electrolyte is 0.5-1.8×10⁻⁶. -3 S / cm, electronic conductivity ≤6.66×10 -9 S / cm.
[0014] The novel zirconium-based halide inorganic solid electrolyte has an amorphous structure, and cadmium ions and oxygen ions are uniformly dispersed in the amorphous structure without obvious aggregation.
[0015] An all-solid-state lithium-ion battery includes a positive electrode, a negative electrode, a solid electrolyte layer, and a current collector; the solid electrolyte layer is made of a novel zirconium-based halide inorganic solid electrolyte. The novel zirconium-based halide inorganic solid electrolyte can be mixed with the positive electrode active material as an additive to form a composite positive electrode.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention uses Li₂ZrCl₆ as the matrix, and employs Cd...2+ Cation doping and O 2- A dual-doping strategy involving anion co-doping, combined with amorphous structure modulation, increased the ionic conductivity of zirconium-based halide solid electrolytes to 1.8 × 10⁻⁶ at 30 °C. -3 S / cm, while electronic conductivity is controlled at ≤6.66×10 -9 The S / cm significantly optimizes the ion transport performance and electronic insulation of the electrolyte, providing core support for the stable cycling at room temperature of all-solid-state lithium-ion batteries; 2. This invention uses low-cost LiCl and ZrCl4 as basic raw materials, without relying on expensive rare earth metals, and the preparation process does not require high-temperature sintering. The process is simple, controllable, and energy-efficient. This electrolyte can be used as a solid electrolyte layer in all-solid-state lithium-ion batteries, or as an additive to form a composite cathode. It is compatible with various cathode systems and Li-In alloy anodes, has strong compatibility, and helps to promote the commercial application of halide solid electrolytes. Attached Figure Description
[0017] Figure 1 The X-ray diffraction pattern of the Li2ZrCl6 solid electrolyte powder prepared in Example 1 of this invention; Figure 2 The electrochemical impedance spectroscopy of the Li2ZrCl6 solid electrolyte powder prepared in Example 1 of this invention is shown. Figure 3 The DC polarization spectrum of the Li2ZrCl6 solid electrolyte powder prepared in Example 1 of this invention; Figure 4 The Li prepared in Example 2 of this invention 2.1 Zr 0.95 Cd 0.05 X-ray diffraction pattern of Cl6 solid electrolyte powder; Figure 5 The Li prepared in Example 2 of this invention 2.1 Zr 0.95 Cd 0.05 Electrochemical impedance spectroscopy of Cl6 solid electrolyte powder; Figure 6 The Li prepared in Example 2 of this invention 2.1 Zr 0.95 Cd 0.05 DC polarization spectrum of Cl6 solid electrolyte powder; Figure 7 The Li prepared in Example 3 of this invention 3.2 ZrCl 4.8 O 1.2 X-ray diffraction pattern of solid electrolyte powder; Figure 8 The Li prepared in Example 3 of this invention3.2 ZrCl 4.8 O 1.2 DC polarization spectrum of solid electrolyte powder; Figure 9 The Li prepared in Example 4 of this invention 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2 X-ray diffraction pattern of solid electrolyte powder; Figure 10 The Li prepared in Example 4 of this invention 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2 Electrochemical impedance spectroscopy of solid electrolyte powder; Figure 11 The Li prepared in Example 4 of this invention 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2 DC polarization spectrum of solid electrolyte powder; Figure 12 The Li prepared in Example 5 of this invention 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 X-ray diffraction pattern of solid electrolyte powder; Figure 13 The Li prepared in Example 5 of this invention 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 Electrochemical impedance spectroscopy of solid electrolyte powder; Figure 14 The Li prepared in Example 5 of this invention 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 DC polarization spectrum of solid electrolyte powder. Detailed Implementation
[0018] To enable those skilled in the art to better understand the present invention, the technical solution of the present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0019] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual images. They should not be construed as limiting the scope of this application. To better illustrate the embodiments of the present invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual dimensions of the product. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.
[0020] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "inner," and "outer" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present application. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.
[0021] In the description of this invention, unless otherwise explicitly specified and limited, the term "connection" or similar designation indicating a connection between components should be interpreted broadly. For example, it can refer to a fixed connection, a detachable connection, or an integral part; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can refer to the internal communication between two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0022] Example 1: like Figure 1-14 As shown, this invention discloses a novel method for preparing zirconium-based halide inorganic solid electrolytes, the method comprising the following steps: Step 1: Under an inert protective atmosphere, weigh lithium source, zirconium source, cadmium source and oxygen source according to stoichiometric ratio; mix the raw materials in an agate mortar and perform pulsed ultrasonic-assisted gradient grinding to obtain an activated precursor mixture; Step 2: Add the precursor mixture to a zirconia ball mill jar, and ball mill it by applying an alternating electromagnetic field, while simultaneously and dynamically controlling the pressure and temperature inside the ball mill jar during the ball milling process; Step 3: After ball milling, the powder is transferred to an agate mortar and ground for 10-30 minutes, preferably 10-20 minutes, and more preferably 15 minutes, under an inert atmosphere to prevent powder agglomeration. Then, low-temperature plasma activation treatment is performed to collect the inorganic solid electrolyte powder. The general chemical formula of the novel zirconium-based halide inorganic solid electrolyte is Li a Zrb Cd c Cl x O y The microstructure is Zr 4+ Cd 2+ Amorphous structures with mixed arrangement.
[0023] Specifically, steps 1, 2, and 3 all need to be performed in a glove box filled with argon gas.
[0024] Furthermore, in step 1, the lithium source is LiCl, the zirconium source is ZrCl4, the cadmium source is CdCl2, and the oxygen source is Li2O; and the amount of CdCl2 and Li2O weighed is 2-10% excess based on stoichiometry to compensate for losses during weighing and grinding; the inert protective atmosphere is argon, with an oxygen content <0.01ppm and a water content <0.01ppm; in step 2, the grinding jar and grinding beads are both made of zirconium oxide; the diameter of the grinding beads used is 3-10mm; the ball-to-material ratio ranges from 10 to 40:1, i.e., the ratio of the total mass of the grinding beads to the total mass of the material to be ground is controlled within the range of 10:1 to 40:1.
[0025] Specifically, the ball mill is an all-around planetary ball mill that can rotate 360 degrees while rotating at high speed on a plane; both the grinding jar and the grinding balls are made of zirconium oxide, and the preferred mass ratio of the grinding balls is 8mm:5mm:3mm=2:3:5; the ball-to-material ratio ranges from 10 to 40:1, preferably from 20 to 40:1, and even more preferably from 40:1.
[0026] Furthermore, the pulsed ultrasound-assisted gradient grinding process in step 1 includes grinding at a speed of 50-100 rpm for 5-10 minutes; then, intermittent pulsed ultrasound and high-speed grinding are performed simultaneously, wherein the pulsed ultrasound power is 150-250W, the frequency is 20-40kHz, and the cycle is 30 seconds working followed by a 30-second pause; the high-speed grinding is performed at a speed of 200-300 rpm for 5-20 minutes.
[0027] Specifically, the implementation method of pulsed ultrasonic-assisted gradient grinding is to place the agate mortar on the oscillation table of the ultrasonic generator. The ultrasonic energy is transferred to the raw material in the mortar through the oscillation table, realizing the synchronous and coordinated high-speed grinding stage of ultrasonic and grinding accompanied by ultrasonic-mechanical resonance regulation with a resonance frequency of 50-80Hz, which improves the crushing and mixing uniformity of precursor particles.
[0028] Furthermore, the alternating electromagnetic field in step 2 is a sinusoidal alternating electromagnetic field with a magnetic field strength of 20-40 mT and a frequency of 100-200 Hz; the pressure inside the ball mill jar is 0.1-0.2 MPa; the ball milling process is divided into two stages. In the first stage, the magnetic field strength is 20-25 mT, the frequency is 100-150 Hz, the temperature is 25℃, and the rotation speed is 350-400 rpm, using a bidirectional ball milling mode for 8-12 hours. In the second stage, the magnetic field strength is 30-40 mT, the frequency is 150-200 Hz, the temperature is 45-55℃, and the rotation speed is 500-550 rpm, using a bidirectional ball milling mode for 12-20 hours. During the ball milling process, the equipment is shut down every 4 hours, the agglomerated powder on the inner wall of the ball mill container is scraped off, and argon gas is added.
[0029] Specifically, use a spatula to scrape the powder that has clumped on the inner wall, bottom, and lid of the ball mill jar to prevent insufficient high-energy ball milling in the future; an electromagnetic field shielding layer is installed on the outer wall of the ball mill jar to ensure that the magnetic field acts on the raw material inside the jar in a concentrated manner and to prevent magnetic field leakage.
[0030] Furthermore, the bidirectional ball milling mode involves first rotating in either clockwise or counterclockwise direction for 5-30 minutes, pausing for 5-30 minutes, then rotating in the opposite direction for 5-30 minutes, pausing for 5-30 minutes, and repeating this cycle.
[0031] Furthermore, the low-temperature plasma activation treatment in step 3 is carried out in an argon atmosphere, with a plasma activation power of 80-150W and a treatment time of 3-8 minutes.
[0032] Specifically, post-activation treatment is performed under an argon atmosphere. During the treatment, the argon flow rate is controlled at 8-15 sccm. This flow rate range is sufficient to maintain stable plasma glow discharge and ensure the purity of the treatment atmosphere, while avoiding powder splashing due to excessive gas flow. The plasma treatment power is 80-150W, and the treatment time is 3-8 minutes. After treatment, the powder is collected under an inert atmosphere to obtain the high-performance zirconium-based halide inorganic solid electrolyte.
[0033] A novel zirconium-based halide inorganic solid electrolyte is prepared by a novel method for preparing zirconium-based halide inorganic solid electrolytes. The general chemical formula of the novel zirconium-based halide inorganic solid electrolyte is Li. a Zr b Cd c Cl x O y Where 2≤a≤4, 0.8≤b≤1, 0≤c≤0.2, 4≤x≤6, 0≤y≤1.6; at a temperature of 30℃, the ionic conductivity of the inorganic solid electrolyte is 0.5-1.8×10⁻⁶. -3 S / cm, electronic conductivity ≤6.66×10 -9S / cm. Specifically, c and y are preferably 0.05≤c≤0.10 and 0.7≤y≤1.2, and more preferably c=0.05 and 0.9≤y≤1.2.
[0034] The novel zirconium-based halide inorganic solid electrolyte has an amorphous structure, and cadmium and oxygen ions are uniformly dispersed in the amorphous structure without obvious aggregation.
[0035] An all-solid-state lithium-ion battery includes a positive electrode, a negative electrode, a solid electrolyte layer, and a current collector; the solid electrolyte layer is made of a novel zirconium-based halide inorganic solid electrolyte. The novel zirconium-based halide inorganic solid electrolyte can be mixed with the positive electrode active material as an additive to form a composite positive electrode. Specifically, the active material of the positive electrode includes any one of ternary materials, LiCoO2, and lithium-rich manganese-based materials; the negative electrode is a Li-In alloy. Example 1
[0036] In a glove box filled with an argon protective atmosphere (water content < 0.01 ppm, oxygen content < 0.01 ppm), LiCl and ZrCl4 were weighed according to the stoichiometric ratio. The raw materials were mixed and placed in an agate mortar for pulsed ultrasonic-assisted gradient grinding. First, grinding was performed at 80 rpm for 8 minutes. Then, intermittent pulsed ultrasonic grinding and high-speed grinding were simultaneously activated. The ultrasonic power was 200 W and the frequency was 30 kHz. The process was repeated in a cycle of 30 seconds on and 30 seconds off, grinding at 250 rpm for 2 minutes. The total grinding time was [not specified]. After 10 minutes, 3g of activated precursor mixture was obtained. The 3g precursor mixture was transferred to a 100mL zirconia ball milling jar. Zirconia ball milling beads with a diameter of 5-10mm were added according to a ball-to-material ratio of 40:1, with a specific ratio of 10mm:5mm=1:2. The jar was then sealed. The jar was placed in an all-around planetary ball mill and a ball milling process with alternating electromagnetic field assistance and dynamic pressure control was adopted. A sinusoidal alternating electromagnetic field with a magnetic field strength of 22mT and a frequency of 120Hz was applied simultaneously, and the pressure inside the jar was dynamically adjusted to 0.15MPa. The ball milling process consisted of two stages. The first stage involved a bidirectional milling cycle at 25°C, 400 rpm, 22 mT magnetic field strength, and 120 Hz, lasting 10 hours. The second stage involved a bidirectional milling cycle at 50°C, 550 rpm, 35 mT magnetic field strength, and 180 Hz, lasting 22 hours. The bidirectional milling cycle consisted of a 15-minute clockwise rotation followed by a 5-minute pause, then a 15-minute counter-clockwise rotation followed by a 5-minute pause, repeated cyclically, for a total milling time of 32 hours. During the milling process, the equipment was shut down every 4 hours. Agglomerated powder was scraped from the inner wall, bottom, and lid of the milling jar using a spatula, and argon gas was added to maintain stable pressure inside the jar.
[0037] After ball milling, the powder was transferred to an agate mortar and ground for 10 minutes under an argon protective atmosphere. Then, it was subjected to low-temperature plasma activation treatment with a power of 120W and a time of 5 minutes to obtain Li2ZrCl6 inorganic solid electrolyte powder.
[0038] X-ray diffraction (XRD) was performed on the prepared Li₂ZrCl₆ solid electrolyte using Cu-Ka rays as the XRD source, with a testing range of 10–80°. Before testing, the solid electrolyte was sealed with a Capton membrane in a glove box filled with argon to prevent contact with air during the test. Comparison of the obtained XRD pattern with a standard PDF card revealed that the Li₂ZrCl₆ solid electrolyte obtained in Example 1 using the preparation method provided by this invention is a pure phase without impurities, i.e., a hexagonal close-packed triangular phase.
[0039] In a glove box filled with an argon protective atmosphere, 120 mg of the prepared Li₂ZrCl₆ solid electrolyte powder was first weighed and placed inside the mold battery. It was then cold-pressed into a sheet with a thickness of 572 μm under a pressure of 380 MPa. Electrochemical impedance spectroscopy (EIS) and DC polarization tests were then performed on the mold battery at 30 °C using a Princeton electrochemical workstation to obtain the ionic and electronic conductivity of the solid electrolyte. According to the EIS results, the ionic conductivity of the inorganic solid electrolyte Li₂ZrCl₆ obtained by high-energy mechanical ball milling at 30 °C is 7.8 × 10⁻⁶. -4 S cm -1 The electronic conductivity is 3.76 × 10⁻⁶. -10 The S / cm ratio demonstrates that Li2ZrCl6 is a solid electrolyte with good ionic conductivity and electronic insulation.
[0040] Example 2 In a glove box under an argon protective atmosphere, LiCl, ZrCl4, and CdCl2 were weighed according to stoichiometric ratios, with CdCl2 added in 5% excess to compensate for losses during weighing and grinding. The raw materials were placed in an agate mortar for pulsed ultrasonic-assisted gradient grinding. First, grinding was performed at 80 rpm for 8 minutes, then intermittent pulsed ultrasonic grinding and high-speed grinding were simultaneously activated. The ultrasonic power was 200 W, the frequency was 30 kHz, and the operation was repeated in a 30-second work cycle followed by a 30-second pause. Grinding was performed at 250 rpm for 2 minutes, for a total grinding time of 10 minutes, yielding 3g of activated precursor mixture.
[0041] Transfer 3g of the precursor mixture to a 100mL zirconia ball mill jar. Add zirconia grinding beads with a diameter of 5-10mm at a ball-to-bead ratio of 40:1 (specifically, the ratio of 10mm:5mm = 1:2). Seal the jar. Place the jar into an omnidirectional planetary ball mill and employ a ball milling process assisted by alternating electromagnetic field and dynamic pressure control. Simultaneously apply a sinusoidal alternating electromagnetic field with a magnetic field strength of 22mT and a frequency of 120Hz, dynamically adjusting the pressure inside the jar to 0.15MPa. The ball milling process consisted of two stages. The first stage involved a bidirectional milling cycle at 25°C, 400 rpm, 22 mT magnetic field strength, and 120 Hz, lasting 10 hours. The second stage involved a bidirectional milling cycle at 50°C, 550 rpm, 35 mT magnetic field strength, and 180 Hz, lasting 22 hours. The bidirectional milling cycle consisted of rotating clockwise for 15 minutes, pausing for 5 minutes, then rotating counter-clockwise for 15 minutes, pausing for 5 minutes, and repeating this cycle, for a total milling time of 32 hours. During the milling process, the equipment was shut down every 4 hours. Agglomerated powder was scraped from the inner wall, bottom, and lid of the milling jar using a spatula, and argon gas was added to maintain stable pressure inside the jar.
[0042] After ball milling, the powder was transferred to an agate mortar and ground for 10 minutes under argon protection. Subsequently, it underwent low-temperature plasma activation treatment in an argon atmosphere at a power of 120W for 5 minutes to obtain Li. 2.1 Zr 0.95 Cd 0.05 Cl6 inorganic solid electrolyte powder.
[0043] For the prepared Li 2.1 Zr 0.95 Cd 0.05 X-ray diffraction (XRD) tests were performed on the Cl6 solid electrolyte using Cu-Ka rays as the X-ray source, with a testing range of 10-80°. Before testing, the solid electrolyte was sealed with a Capton membrane in a glove box filled with an argon protective atmosphere to prevent contact with air during the test. Comparison of the obtained XRD pattern with a standard PDF card revealed that the Li obtained in Example 2 using the preparation method provided by this invention… 2.1 Zr 0.95 Cd 0.05 Cl6 solid electrolyte is a pure phase without impurities, namely a hexagonal close-packed triangular phase.
[0044] In a glove box filled with an argon protective atmosphere, the prepared Li was first weighed out. 2.1 Zr 0.95 Cd 0.05120 mg of Cl6 solid electrolyte powder was packed into the mold battery and then cold-pressed into a sheet with a thickness of 621 μm under a pressure of 380 MPa. Electrochemical impedance spectroscopy (EIS) and DC polarization tests were then performed on the mold battery at 30 °C using a Princeton electrochemical workstation to obtain the ionic and electronic conductivity of the solid electrolyte. Based on the EIS results, the inorganic solid electrolyte Li was obtained by high-energy mechanical ball milling at 30 °C. 2.1 Zr 0.95 Cd 0.05 The ionic conductivity of Cl6 is 9.8 × 10⁻⁶. -4 Scm -1 The electronic conductivity is 6.83 × 10⁻⁶. -10 S / cm, proving Li 2.1 Zr 0.95 Cd 0.05 Cl6 is a solid electrolyte with good ionic conductivity and electronic insulation.
[0045] Example 3 In a glove box under an argon protective atmosphere, LiCl, ZrCl4, and Li2O were weighed according to stoichiometric ratios, with Li2O added in 5% excess to compensate for losses during weighing and grinding. The raw materials were placed in an agate mortar for pulsed ultrasonic-assisted gradient grinding. First, grinding was performed at 80 rpm for 8 minutes, followed by simultaneous intermittent pulsed ultrasonic grinding and high-speed grinding. The ultrasonic power was 200 W, the frequency was 30 kHz, and the operation was repeated in a 30-second work cycle followed by a 30-second pause. The high-speed grinding speed was 250 rpm for 2 minutes, for a total grinding time of 10 minutes, yielding 3g of precursor mixture.
[0046] Transfer 3g of the precursor mixture to a 100mL zirconia ball mill jar, add 5mm diameter zirconia grinding beads at a ball-to-material ratio of 40:1, and seal the jar. Place the jar in an omnidirectional planetary ball mill and employ a ball milling process assisted by alternating electromagnetic field and dynamic pressure control. Simultaneously apply a sinusoidal alternating electromagnetic field with a magnetic field strength of 22mT and a frequency of 120Hz, dynamically adjusting the pressure inside the jar to 0.15MPa. The ball milling is divided into two stages. In the first stage, the temperature is 25℃, the rotation speed is 400rpm, the magnetic field strength is 22mT, and the frequency is 120Hz, using a bidirectional ball milling mode for 10 hours. In the second stage, the temperature is 50℃, the rotation speed is 550rpm, the magnetic field strength is 35mT, and the frequency is 180Hz, using the same bidirectional ball milling mode for 22 hours. The bidirectional ball milling mode involves rotating clockwise for 15 minutes, pausing for 5 minutes, then rotating counterclockwise for 15 minutes, pausing for 5 minutes, and repeating this cycle, for a total ball milling time of 32 hours. During the ball milling process, the equipment is shut down every 4 hours. The agglomerated powder on the inner wall, bottom and lid of the ball milling jar is scraped off with a spatula, and argon gas is added to maintain stable pressure inside the jar.
[0047] After ball milling, the powder was transferred to an agate mortar and ground for 10 minutes under argon protection. Subsequently, it underwent low-temperature plasma activation treatment in an argon atmosphere at a power of 120W for 5 minutes, and Li was collected. 3.2 ZrCl 4.8 O 1.2 Inorganic solid electrolyte powder.
[0048] For the prepared Li 3.2 ZrCl 4.8 O 1.2 X-ray diffraction (XRD) was performed on the solid electrolyte using Cu-Ka rays as the XRD source, with a testing range of 10-80°. Before testing, the solid electrolyte was sealed with a Capton membrane in a glove box filled with an argon protective atmosphere to prevent contact with air during the test. Comparison of the obtained XRD pattern with a standard PDF card revealed that the Li prepared by the method provided in Example 3... 3.2 ZrCl 4.8 O 1.2 Except for a portion of the LiCl main peak, the solid electrolyte exists in an amorphous disordered state.
[0049] In a glove box filled with an argon protective atmosphere, the prepared Li was first weighed out. 3.2 ZrCl 4.8 O 1.2 120 mg of solid electrolyte powder was packed into a mold battery and then cold-pressed into a sheet with a thickness of 600 μm under a pressure of 380 MPa. The mold battery was then subjected to DC polarization testing at 30 °C using a Princeton electrochemical workstation to obtain the electronic conductivity of the solid electrolyte. Based on the results of electrochemical impedance spectroscopy, the inorganic solid electrolyte Li was obtained by high-energy mechanical ball milling at 30 °C. 3.2 ZrCl 4.8 O 1.2 Its electronic conductivity is 5.64 × 10⁻⁶. -10 S / cm, proving Li 3.2 ZrCl 4.8 O 1.2 It is a solid electrolyte with good ionic conductivity and electronic insulation.
[0050] Example 4 In a glove box under an argon protective atmosphere, LiCl, ZrCl4, CdCl2, and Li2O were weighed according to stoichiometric ratios. The raw materials were placed in an agate mortar and subjected to pulsed ultrasonic-assisted gradient grinding. First, grinding was performed at 80 rpm for 8 minutes, and then intermittent pulsed ultrasonic grinding and high-speed grinding were simultaneously turned on. The ultrasonic power was 200W and the frequency was 30kHz, with a cycle of 30 seconds of operation and 30 seconds of pause. The high-speed grinding speed was 250 rpm for 7 minutes, and the total grinding time was 15 minutes to obtain 3g of precursor mixture.
[0051] Transfer 3g of the precursor mixture to a 100mL zirconia ball mill jar. Add zirconia grinding beads with a diameter of 3-8mm at a ball-to-bead ratio of 40:1 (specifically, the ratio of grinding beads is 8mm:5mm:3mm = 2:3:5). Seal the ball mill jar. Place the ball mill jar into an omnidirectional planetary ball mill and employ a ball milling process assisted by alternating electromagnetic field and dynamic pressure control. Simultaneously apply a sinusoidal alternating electromagnetic field with a magnetic field strength of 22mT and a frequency of 120Hz, and dynamically adjust the pressure inside the jar to 0.15MPa. The ball milling process consisted of two stages. The first stage involved a bidirectional milling cycle at 25°C, 400 rpm, 22 mT magnetic field strength, and 120 Hz, lasting 10 hours. The second stage involved a bidirectional milling cycle at 50°C, 550 rpm, 35 mT magnetic field strength, and 180 Hz, lasting 22 hours. The bidirectional milling cycle consisted of rotating clockwise for 15 minutes, pausing for 5 minutes, then rotating counterclockwise for 15 minutes, pausing for 5 minutes, and repeating this cycle, for a total milling time of 32 hours. During the milling process, the equipment was shut down every 4 hours. Agglomerated powder was scraped from the inner wall, bottom, and lid of the milling jar using a spatula, and argon gas was added to maintain stable pressure inside the jar.
[0052] After ball milling, the powder was transferred to an agate mortar and ground for 15 minutes under argon protection. Subsequently, it underwent low-temperature plasma activation treatment in an argon atmosphere at a power of 120W for 5 minutes, and Li was collected. 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2 Inorganic solid electrolyte powder.
[0053] For the prepared Li 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2X-ray diffraction (XRD) was performed on the solid electrolyte using Cu-Ka rays as the XRD source, with a testing range of 10-80°. Before testing, the solid electrolyte was sealed with a Capton membrane in a glove box filled with an argon protective atmosphere to prevent contact with air during the test. Comparison of the obtained XRD pattern with a standard PDF card revealed that the Li prepared by the method provided in this invention in Example 4... 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2 Solid electrolytes have an amorphous localized structure with double anion doping, and the increased degree of amorphization is beneficial to the improvement of ionic conductivity.
[0054] In the glove box, first weigh the prepared Li 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2 120 mg of solid electrolyte powder was packed into a mold battery and then cold-pressed into a sheet with a thickness of 600 μm under a pressure of 380 MPa. Electrochemical impedance spectroscopy (EIS) and DC polarization tests were then performed on the mold battery at 30 °C using a Princeton electrochemical workstation to obtain the ionic and electronic conductivity of the solid electrolyte. Based on the EIS results, an inorganic solid electrolyte, Li, was obtained by high-energy mechanical ball milling at 30 °C. 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2 Its ionic conductivity is 1.85 × 10⁻⁶. -3 S cm -1 The electronic conductivity is 5.20 × 10⁻⁶. -10 S / cm, proving Li 3.3 Zr 0.95 Cd 0.05 Cl 4.8 O 1.2 It is a solid electrolyte with good ionic conductivity and electronic insulation.
[0055] Example 5 In a glove box under an argon protective atmosphere, LiCl, ZrCl4, CdCl2, and Li2O were weighed according to stoichiometric ratios, with CdCl2 and Li2O added in 5% excess to compensate for losses during weighing and grinding. The raw materials were placed in an agate mortar for pulsed ultrasonic-assisted gradient grinding. First, grinding was performed at 80 rpm for 8 minutes, followed by simultaneous intermittent pulsed ultrasonic grinding and high-speed grinding. The ultrasonic power was 200W, the frequency was 30kHz, and the operation was repeated in a 30s working, 30s pause cycle. The high-speed grinding speed was 250 rpm for 2 minutes, and the total grinding time was 10 minutes to obtain 3g of precursor mixture.
[0056] Transfer 3g of the precursor mixture to a 100mL zirconia ball mill jar, add 5mm diameter zirconia grinding beads at a ball-to-material ratio of 40:1, and seal the jar. Place the jar in an omnidirectional planetary ball mill and employ a ball milling process assisted by alternating electromagnetic field and dynamic pressure control. Simultaneously apply a sinusoidal alternating electromagnetic field with a magnetic field strength of 22mT and a frequency of 120Hz, dynamically adjusting the pressure inside the jar to 0.15MPa. The ball milling is divided into two stages. In the first stage, the temperature is 25℃, the rotation speed is 400rpm, the magnetic field strength is 22mT, and the frequency is 120Hz, using a bidirectional ball milling mode for 10 hours. In the second stage, the temperature is 50℃, the rotation speed is 550rpm, the magnetic field strength is 35mT, and the frequency is 180Hz, using the same bidirectional ball milling mode for 22 hours. The bidirectional ball milling mode involves rotating clockwise for 15 minutes, pausing for 5 minutes, then rotating counterclockwise for 15 minutes, pausing for 5 minutes, and repeating this cycle, for a total ball milling time of 32 hours. During the ball milling process, the equipment is shut down every 4 hours. The agglomerated powder on the inner wall, bottom and lid of the ball milling jar is scraped off with a spatula, and argon gas is added to maintain stable pressure inside the jar.
[0057] After ball milling, the powder was transferred to an agate mortar and ground for 10 minutes under argon protection. Subsequently, it underwent low-temperature plasma activation treatment in an argon atmosphere at a power of 120W for 5 minutes, and Li was collected. 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 Inorganic solid electrolyte powder.
[0058] For the prepared Li 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9X-ray diffraction (XRD) was performed on the solid electrolyte using Cu-Ka rays as the XRD source, with a testing range of 10-80°. Before testing, the solid electrolyte was sealed with a Capton membrane in a glove box filled with an argon protective atmosphere to prevent contact with air during the test. Comparison of the obtained XRD pattern with a standard PDF card revealed that the Li prepared by the method provided in Example 5... 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 The diffraction peak intensity of the solid electrolyte is significantly reduced, indicating that the solid electrolyte has amorphous characteristics.
[0059] In a glove box filled with an argon protective atmosphere, the prepared Li was first weighed out. 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 120 mg of solid electrolyte powder was packed into a mold battery and then cold-pressed into a sheet with a thickness of 600 μm under a pressure of 380 MPa. Electrochemical impedance spectroscopy (EIS) and DC polarization tests were then performed on the mold battery at 30 °C using a Princeton electrochemical workstation to obtain the ionic and electronic conductivity of the solid electrolyte. Based on the EIS results, an inorganic solid electrolyte, Li, was obtained by high-energy mechanical ball milling at 30 °C. 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 Its ionic conductivity is 1.91 × 10⁻⁶. -3 S cm -1 The electronic conductivity is 6.66 × 10⁻⁶. -9 S / cm, proving Li 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 It is a solid electrolyte with good ionic conductivity and electronic insulation.
[0060] As can be seen from the above embodiments, the novel zirconium-based halide inorganic solid electrolyte obtained by the present invention has an ionic conductivity as high as 1.8 × 10⁻⁶ at 30 °C. -3 The S / cm value is high, while the electronic conductivity is only 5.3 × 10⁻⁶. -10 A S / cm ratio indicates that the resulting solid-state electrolyte is an excellent ionic conductor, enabling all-solid-state lithium-ion batteries assembled with it to achieve stable cycling at room temperature. Furthermore, the absence of expensive rare-earth elements and the simplicity of the synthesis method significantly reduce the production cost of solid-state electrolytes, facilitating the commercial application of halide solid-state electrolytes.
[0061] Comparative Example 1 In a glove box under an argon protective atmosphere, LiCl, ZrCl4, CdCl2, and Li2O were weighed according to stoichiometric ratios, with CdCl2 and Li2O added in 5% excess to compensate for losses during weighing and grinding. The raw materials were placed in an agate mortar for pulsed ultrasonic-assisted gradient grinding. First, grinding was performed at 80 rpm for 8 minutes, followed by simultaneous intermittent pulsed ultrasonic grinding and high-speed grinding. The ultrasonic power was 200W, the frequency was 30kHz, and the operation was repeated in a 30s working, 30s pause cycle. The high-speed grinding speed was 250 rpm for 2 minutes, and the total grinding time was 10 minutes to obtain 3g of precursor mixture.
[0062] Transfer 3g of the precursor mixture to a 100mL zirconia ball mill jar, add 5mm diameter zirconia grinding beads at a ball-to-material ratio of 40:1, and seal the jar. Place the jar in an omnidirectional planetary ball mill, apply only a fixed-intensity sinusoidal alternating electromagnetic field, and dynamically adjust the pressure inside the jar to 0.15MPa. The ball milling is divided into two stages. In the first stage, the temperature is 25℃, the rotation speed is 400rpm, the magnetic field strength is 22mT, and the frequency is 120Hz, using a bidirectional ball milling mode, and the milling is carried out cyclically for 10 hours. In the second stage, the temperature is 50℃, the rotation speed is 550rpm, the magnetic field parameters remain unchanged, and the same bidirectional ball milling mode is used, and the milling is carried out for 22 hours. The bidirectional ball milling mode is to rotate clockwise for 15 minutes, pause for 5 minutes, then rotate counterclockwise for 15 minutes, pause for 5 minutes, and repeat the cycle, for a total ball milling time of 32 hours. During the ball milling process, the equipment is shut down every 4 hours, and the agglomerated powder on the inner wall, bottom, and lid of the jar is scraped off with a spatula. Argon gas is added to maintain a stable pressure inside the jar.
[0063] After ball milling, the powder was transferred to an agate mortar and ground for 10 minutes under argon protection. Subsequently, it underwent low-temperature plasma activation treatment in an argon atmosphere at a power of 120W for 5 minutes, and Li was collected. 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 Inorganic solid electrolyte powder.
[0064] The prepared electrolyte was subjected to performance testing. X-ray diffraction patterns showed that its diffraction peak intensity was higher than that of Example 5, indicating insufficient amorphization. The ionic conductivity at 30°C was 0.72 × 10⁻⁶. -3 S / cm, electronic conductivity 8.9×10 -9 S / cm. The results show that when only a single magnetic field is applied, it is impossible to adapt the gradient magnetic field strength to the material reaction requirements of the ball milling stage, resulting in uneven dispersion of doped ions, insufficient formation of amorphous structures, and significantly lower ion transport efficiency than in Example 5.
[0065] Comparative Example 2 In a glove box under an argon protective atmosphere, LiCl, ZrCl4, CdCl2, and Li2O were weighed according to stoichiometric ratios, with CdCl2 and Li2O added in 5% excess to compensate for losses during weighing and grinding. The raw materials were placed in an agate mortar for pulsed ultrasonic-assisted gradient grinding. First, grinding was performed at 80 rpm for 8 minutes, followed by simultaneous intermittent pulsed ultrasonic grinding and high-speed grinding. The ultrasonic power was 200W, the frequency was 30kHz, and the operation was repeated in a 30s working, 30s pause cycle. The high-speed grinding speed was 250 rpm for 2 minutes, and the total grinding time was 10 minutes to obtain 3g of precursor mixture.
[0066] Transfer 3g of the precursor mixture to a 100mL zirconia ball mill jar, add 5mm diameter zirconia grinding beads at a ball-to-material ratio of 40:1, and seal the jar. Place the jar in an omnidirectional planetary ball mill and use a dynamic pressure-controlled milling process, dynamically adjusting the pressure inside the jar to 0.15MPa. The milling is divided into two stages: the first stage is carried out at 25℃ and 400rpm using a bidirectional milling mode for 10 hours; the second stage is carried out at 50℃ and 550rpm using the same bidirectional milling mode for 22 hours. The bidirectional milling mode involves rotating clockwise for 15 minutes, pausing for 5 minutes, then rotating counterclockwise for 15 minutes, pausing for 5 minutes, and repeating this cycle, for a total milling time of 32 hours. During the milling process, the equipment is shut down every 4 hours, and the agglomerated powder on the inner wall, bottom, and lid of the jar is scraped off with a spatula. Argon gas is then added to maintain a stable pressure inside the jar.
[0067] After ball milling, the powder was transferred to an agate mortar and ground for 10 minutes under argon protection. Subsequently, it underwent low-temperature plasma activation treatment in an argon atmosphere at a power of 120W for 5 minutes, and Li was collected. 2.1 Zr 0.95 Cd 0.05 Cl 4.2 O 0.9 Inorganic solid electrolyte powder.
[0068] The prepared electrolyte was subjected to performance testing. X-ray diffraction patterns showed obvious crystallization peaks, weak amorphization characteristics, and Cd was observed. 2+ With O 2- Aggregation phenomenon; ionic conductivity at 30℃ is only 0.45×10⁻⁶. -3 S / cm, electronic conductivity 1.2×10 -8S / cm. The results show that without electromagnetic field assistance, the material is only subjected to mechanical impact force during ball milling, making it difficult to achieve uniform diffusion of doped ions and effective control of amorphous structure. The ionic conductivity and structural uniformity of the electrolyte are significantly worse than those in Example 5.
[0069] Comparison diagram of Example 5 with Comparative Examples 1 and 2 Example 5 (Variable Magnetic Field) 1.91 6.66 Comparative Example 1 (Single Magnetic Field) 0.72 8.90 Comparative Example 2 (No Magnetic Field) 0.45 12.00 The above are merely embodiments of the present invention. The circuits, electronic components, and modules involved are all prior art, fully achievable by those skilled in the art, and require no further explanation. The content protected by this application does not involve improvements to the software and methods. Commonly known structures and characteristics in the solutions are not described in detail here. Those skilled in the art are aware of all common technical knowledge in the field prior to the application date or priority date, are able to access all prior art in that field, and have the ability to apply conventional experimental methods prior to that date. Those skilled in the art can, under the guidance of this application, improve and implement this solution in combination with their own capabilities. Some typical known structures or methods should not be obstacles for those skilled in the art to implement this application. It should be noted that those skilled in the art can make several modifications and improvements without departing from the structure of the present invention. These should also be considered within the scope of protection of the present invention, and will not affect the effectiveness of the implementation of the present invention or the practicality of the patent.
Claims
1. A novel method for preparing zirconium-based halide inorganic solid electrolytes, characterized in that, The method includes the following steps: Step 1: Under an inert protective atmosphere, weigh out the lithium source, zirconium source, cadmium source and oxygen source according to the stoichiometric ratio; The raw materials are mixed and placed in an agate mortar, and subjected to pulsed ultrasonic-assisted gradient grinding to obtain an activated precursor mixture. The pulsed ultrasonic-assisted gradient grinding process includes grinding at 50-100 rpm for 5-10 minutes; then intermittent pulsed ultrasonic and high-speed grinding are performed simultaneously, wherein the pulsed ultrasonic power is 150-250w, the frequency is 20-40kHz, and the cycle is 30 seconds working and then 30 seconds pausing; the high-speed grinding is performed at 200-300 rpm for 5-20 minutes. Step 2: Add the precursor mixture to a zirconia ball mill jar and ball mill it using an alternating electromagnetic field. Simultaneously and dynamically control the pressure and temperature inside the ball mill jar during the ball milling process. The alternating electromagnetic field is a sinusoidal alternating electromagnetic field with a magnetic field strength of 20-40 mT and a frequency of 100-200 Hz. The pressure inside the ball mill jar is 0.1-0.2 MPa. Step 3: After ball milling, the powder is transferred to an agate mortar and ground for 10-30 minutes in an inert atmosphere, followed by low-temperature plasma activation treatment to collect inorganic solid electrolyte powder; the low-temperature plasma activation treatment is carried out in an argon atmosphere, with a plasma activation power of 80-150W and a treatment time of 3-8 minutes. The general chemical formula of the novel zirconium-based halide inorganic solid electrolyte is Li a Zr b Cd c Cl x O y .
2. The method for preparing a novel zirconium-based halide inorganic solid electrolyte as described in claim 1, characterized in that: In step 1, the lithium source is LiCl, the zirconium source is ZrCl4, the cadmium source is CdCl2, and the oxygen source is Li2O; the inert protective atmosphere is argon, wherein the oxygen content is <0.01ppm and the water content is <0.01ppm.
3. The method for preparing a novel zirconium-based halide inorganic solid electrolyte as described in claim 1, characterized in that: In step 2, both the grinding jar and the grinding balls are made of zirconium oxide; the diameter of the grinding balls used is 3-10 mm; and the ball-to-material ratio ranges from 10 to 40:
1.
4. The method for preparing a novel zirconium-based halide inorganic solid electrolyte as described in claim 1, characterized in that: The ball milling process in step 2 is divided into two stages. In the first stage, the magnetic field strength is 20-25 mT, the frequency is 100-150 Hz, the temperature is 25℃, and the rotation speed is 350-400 rpm. The ball milling is carried out in a bidirectional ball milling mode for 8-12 hours. In the second stage, the magnetic field strength is 30-40 mT, the frequency is 150-200 Hz, the temperature is 45-55℃, and the rotation speed is 500-550 rpm. The ball milling is carried out in a bidirectional ball milling mode for 12-20 hours.
5. The method for preparing a novel zirconium-based halide inorganic solid electrolyte as described in claim 4, characterized in that, The bidirectional ball milling mode involves rotating the ball mill in either clockwise or counterclockwise direction for 5-30 minutes, pausing for 5-30 minutes, then rotating it in the opposite direction for 5-30 minutes, pausing for 5-30 minutes, and repeating this cycle.
6. A novel zirconium-based halide inorganic solid electrolyte, characterized in that, The inorganic solid electrolyte is prepared by any one of the methods for preparing a novel zirconium-based halide inorganic solid electrolyte according to claims 1-5, wherein the general chemical formula of the inorganic solid electrolyte is Li. a Zr b Cd c Cl x O y , where 2≤a≤4, 0.8≤b≤1, 0≤c≤0.2, 4≤x≤6, and 0≤y≤1.
6.
7. A novel zirconium-based halide inorganic solid electrolyte as described in claim 6, characterized in that, At a temperature of 30℃, the ionic conductivity of inorganic solid electrolytes is 0.5-1.8×10⁻⁶. -3 S / cm.
8. A fully solid-state lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a solid electrolyte layer, and a current collector; the solid electrolyte layer is made of the novel zirconium-based halide inorganic solid electrolyte as described in any one of claims 6-7, and the novel zirconium-based halide inorganic solid electrolyte can be mixed with the positive electrode active material as an additive to form a composite positive electrode.
Citation Information
Patent Citations
Grinding device for realizing dynamic magnetic field processing and grinding method of grinding device
CN103331693A
Preparation method of Zr-based halide electrolyte with high ionic conductivity
CN119750641A